The effect of forest gaps on the diversity and composition of bacterial communities in mixed-type forest soils across the Carpathian mountains - Nejc Suban; Oliver Maksimović; Nataša Šibanc; Tijana Martinović; Eva Darenova; Matjaž Čater; Tine Grebenc (Acta Silvae et Ligni)
Mixed forests of European beech (Fagus sylvatica L.) and silver fir (Abies alba Mill.) play a vital ecological role in Central and South-Eastern Europe. This study investigates the diversity and composition of soil bacterial communities in these forests, focusing on rhizosphere and bulk soils under varying canopy structures. Soil samples were collected from eight sites along the Carpathian Mountains, including managed forests and the remnants of old growth. Metabarcoding of bacterial communities revealed that alpha diversity (species richness, Shannon index, and evenness) was significantly affected by sampling location but not by forest canopy structure or soil type (rhizosphere and bulk soil). The lowest bacterial diversity was found in the old-growth forest of the Beskidy region, while the highest was recorded in managed forest in Vrancea. Beta diversity analyses showed minimal variation between rhizosphere and bulk soil bacterial communities, with geographic distance being the strongest predictor of community composition. Actinobacteriota and Proteobacteria were the dominant phyla across all sites, with higher relative abundance of Actinobacteriota in all rhizosphere samples compared to bulk soil. Complex combinations of various environmental conditions at each sampling location, including soil parameters (mainly pH and C:N ratio), the age of forest gaps, the type and intensity of disturbances, and species composition of above-ground vegetation, can strongly affect soil bacterial communities. A closer examination of additional environmental variables would be necessary to better explain the observed differences in the diversity and composition of bacterial communities.